The necessity for additional assessment of surveillance indicators of the timeliness of contacting a medical institution with suspected human anthrax in Azerbaijan (One Health & Risk Management, 2023)
Introduction. Cutaneous anthrax in Azerbaijan is an endemic disease among people, particularly in regions with active cattle breeding. Over the period from 2018 to 2022, an average of 12-15 cases were recorded annually, primarily among the rural population. Notably, in 2022, the number of confirmed cases experienced a significant increase. Surveillance for anthrax, along with other infectious diseases, is conducted through the electronic surveillance system for infectious diseases (EIDSS).Aim. To assess the reason for the increase in the number of anthrax cases in Azerbaijan, utilizing surveillance timeliness indicators.Material and methods. We conducted an analysis of the electronic database in EIDSS of the Ministry of Health, focusing on initially reported cases of cutaneous anthrax among humans for the year 2022. The surveillance system was assessed, incorporating timeliness indicators, such as the date when the patient first sought care, the urgency of notification, case entry, initiation of epidemiological investigations, and the completeness of information in the fields related to collected and tested samples. The conventionally assumed threshold value for surveillance indicators is 80% of all cases reported to the system. Laboratory confirmation of samples from suspected cases is performed using both the PCR method and bacteriological methods. Methodological documents used for the evaluation included the “Rules for the Surveillance and Control of Especially Dangerous Infections” (Ministry of Health, Azerbaijan) and the “Updated Guidelines for Evaluating Public Health Surveillance Systems” (CDC, Atlanta).Results. In 2022, a total of 58 human cases of cutaneous anthrax were reported in EIDSS, with 25 cases confirmed by positive laboratory results. Further investigation into cases with negative laboratory results revealed that some patients had self-administered antibiotics and ointments before seeking medical attention. Despite clinical symptoms being present among cases with negative test results (e.g., papules in 91% of cases) and significant risk factors (such as handling meat in 24.2% of cases), there was a notable difference in the timeliness of seeking medical care (p
Keywords: EIDSS; Anthrax; surveillance indicators; timeliness of initial visit to the doctor